ANALISIS PENGGUNAAN LEARNING MANAGEMENT SYSTEM (LMS) MENGGUNAKAN DELONE & MCLEAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI FAKULTAS TEKNIK UNIVERSITAS SEHATI INDONESIA - Hamidah, Siti Nur; Anggara, Ikbal (Jurnal Inkofar, 2025)
Learning Management System (LMS) is a learning method based on E-learning. The purpose of this study is to analyze the relationship between several factors that support the utilization, impact, and development of LMS usage. Data collection using sampling techniques on students of the Faculty of Engineering, Sehati Indonesia University. The method used in this study used a quantitative study with the Delone & McLean model consisting of 6 variables that are compared, namely system quality, information quality, service quality, use, user satisfaction and net benefit. Research analysis using SEM-PLS. The results of the study indicate that there is a strong and positive relationship between the System Quality (SQ) and Service Quality (SeQ) variables that have a positive effect on customer satisfaction or User Satisfaction (SAT), but also in the use of this LMS has several challenges with the low influence of system use on satisfaction and benefits, indicating the need for efforts to improve literacy and digital skills among students and lecturers. The implications of this study suggest the need for technical support and more optimal and intensive training